If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -3 + 2 + 5 Combine like terms: -3 + 2 = -1 y = -1 + 5 Combine like terms: -1 + 5 = 4 y = 4 Solving y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 4
| (3v+5)(8+v)=0 | | 3r-18=3 | | K^2+7x=0 | | -13/5+21/2x=-29/40 | | 25(-8)= | | 2a-6+25=10a | | x+50+x+40+90=180 | | 5r+25=40 | | 6x-7=-2x-9 | | b+10=2b-20 | | bx-a=ac | | 10x=ex-28 | | v^4-13v^3+36v^2=0 | | 15*ln(1+.5x)=ln(2+15x) | | 2(2x+1)=3x-4(1-x) | | 6x+24=6x+12 | | y+y^2+1=14 | | -18(-4)= | | 1.3x-0.28=-2.1 | | 48n-9n^2=36 | | -13+y+y^2=0 | | 0=5x^4-2x^2-4 | | -400.00x+4000=0.00 | | -b+ax=cb | | 3a+5(a-4)= | | -4.5=-.5(x-7.1) | | 10x-23=-123 | | (v^2-13v-36)=0 | | -29+s=-58 | | v^2(v^2-13v-36)=0 | | 4-6p+5p= | | ax-b=cb |